Patients’ general satisfaction with the appearance of anterior maxillary teeth - Lajnert, Vlatka; Kovačević Pavičić, Daniela; Pezo, Hrvoje; Stevanović, Aleksandra; Jović, Tatjana; Šnjarić, Damir; Muhić, Edin (Vojnosanitetski pregled, 2017)
Background/Aim. Dental appearance plays an important role in practically all personal social interactions. The main factors that define the dental appearance are tooth colour, shape and position, quality of restoration, and the general position of the teeth in arch, especially in the anterior region. The aim of this study was to evaluate the impact of dental status (tooth shape, fracture, dental and prosthetic restorations and presence of plaque) on patient's satisfaction with the dental appearance, controlling for the age and gender. Methods. A total of 700 Caucasian subjects (439 women) aged 18–86 (median 45 years) participated in the cross-sectional study. Study included clinical examination and self-administrated questionnaire based on self-perceived aesthetics and satisfaction with the appearance of their maxillary anterior teeth. Results. A regression analysis demonstrated that presence of dental plaque, tooth fracture, composite fillings and crowns had significant independent contribution and were negative predictors of satisfaction with teeth appearance. Participants with presence of plaque on upper teeth (p
Keywords: esthetics; dental; patient satisfaction; surveys and questionnaires; age factors; dental plaque; dental restoration; permanent